MORPHOFUNCTIONAL CHANGES OF SCIATIC NERVE IN TRAUMATIC INJURY AND PECULIARITIES OF ITS REPARATIVE ALTERATIONS - Yurakh, O.M.; Popadynets, O.H.; Yurakh, H.Yu.; Hryshchuk, M.I.; Dubyna, N.M. (World of Medicine and Biology, 2016)
Research is devoted to the study of the processes of regeneration and degeneration, state of microcirculatory elements of the sciatic nerve in terms of laser irradiation after its damage. The experiment was performed on 30 rabbits. Under ether anesthesia in the middle third of the thigh the sciatic nerve was cut, the bleeding was stopped, and later the epineural raphe was sutured. After surgery the laser ray was directed onto the back of the thigh in the projection of the sciatic nerve. Irradiation was performed daily with helium-neon laser LH-75 with a capacity of 20 mV at a density of luminous power of 2.5 mW/cm for 15 days. Number of myelinated, non-myelinated fibers and intra-neural vessels were studied in 25 animals during the 7th, 15th, 30th, 90th, 180th days. Results of the study show that low-energy laser irradiation enhances reparative processes in the damaged nerve. The time of ascending degeneration in the proximal part of the nerve is markedly reduced; secondary degeneration of nerve fibers is more intense. There is a moderate expansion of all parts of hemo-microcirculatory bed; there is more intense vascularization of the injured nerve.
Keywords: sciatic nerve; trauma; degeneration; regeneration